2018
DOI: 10.1073/pnas.1718662115
|View full text |Cite
|
Sign up to set email alerts
|

High integrin α V β 6 affinity reached by hybrid domain deletion slows ligand-binding on-rate

Abstract: The role of the hybrid domain in integrin affinity regulation is unknown, as is whether the kinetics of ligand binding is modulated by integrin affinity state. Here, we compare cell surface and soluble integrin αβ truncation mutants for ligand-binding affinity, kinetics, and thermodynamics. Removal of the integrin transmembrane/cytoplasmic domains or lower legs has little effect on αβ affinity, in contrast to β integrins. In integrin opening, rearrangement at the interface between the βI and hybrid domains is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Mn 2+ increases affinity of αVβ6 in part by stabilizing headpiece opening 12 . Mn 2+ boosted affinity of native αVβ6 by 12-fold and of αVβ8 by 2-fold, correlating with the lack of hybrid domain swing-out in αVβ8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mn 2+ increases affinity of αVβ6 in part by stabilizing headpiece opening 12 . Mn 2+ boosted affinity of native αVβ6 by 12-fold and of αVβ8 by 2-fold, correlating with the lack of hybrid domain swing-out in αVβ8.…”
Section: Discussionmentioning
confidence: 99%
“…Higher affinity results from tightening of the ligand-binding site in the integrin β-subunit βI domain at the β1-α1 loop and α1-helix around the metal ion-dependent adhesion site (MIDAS) (Fig. 1b, c) 11,12 .
Fig. 1Overall integrin conformational states.
…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism for TGFβ activation in chondrocytes, particularly in an active mechanical environment, has not been studied. It has been shown that the arginylglycylaspartic acid (RGD) motif in LAP is the natural ligand for the αV subunit containing integrins 43 , 44 . Cell contractile forces may induce a conformational change of LAP and consequent TGFβ activation through the bond between αV integrins and the RGD sequence in LAP 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have emphasized the importance of force in regulating integrin adhesiveness (Alon & Dustin, 2007;Astrof et al, 2006;Li & Springer, 2017;Nordenfelt et al, 2016;Nordenfelt et al, 2017;Sun et al, 2019;Zhu et al, 2008). Recent measurements of the intrinsic ligand-binding affinity of each conformational state and the equilibria linking them enabled a thermodynamic comparison of integrin activation models (Li & Springer, 2017, 2018Li et al, 2017). Remarkably, only the combination of adaptor binding and cytoskeletal force can activate integrins in an ultra-sensitive manner, with the switch between on and off occurring over a narrow range of signal input {Kuriyan, 2012 #24442}; the large increase in length between the bent and extended conformations (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…If subsequent conformational change to the high affinity state is rapid, fast ligand binding kinetics to the low-affinity state efficiently couples ligand binding to stabilization by applied force of the high-affinity state, which has a long lifetime (Yakovenko, 2015). Work from our group on integrin αVβ6 showed that removal of the hybrid domain in the αVβ6 head resulted in a 50-fold increase in affinity for ligand yet decreased the apparent on-rate of ligand binding (Dong et al, 2018) suggesting that the open conformation has a lower on-rate than the BC and EC states. However, the intrinsic ligand-binding kinetics for each state of integrin αVβ6 could not be determined due to the lack of tools to stabilize specific conformational states.…”
Section: Introductionmentioning
confidence: 99%